C‐F bond activation by saturated NHC: mesoionic compound formation and its unprecedented adduct with B(C6F5)3 - Pait, M.; Kundu, G.; Tothadi, S.; Karak, S.; Jain, S.; Vanka, K.; Sen, S. S. (Angewandte Chemie - International Edition, 2019)
The reaction of SIPr, [1,3‐bis(2,6‐diisopropylphenyl)‐imidazolin‐2‐ylidene] (1), with C6F6 led to the formation of an unprecedented mesoionic compound (2). The formation of 2 is made accessible by deprotonation of the SIPr backbone with simultaneous elimination of HF. The C−F bond para to the imidazolium ring in 2 is only of 1.258(4) Å, which is the one of the shortest structurally authenticated C−F bonds known to date. The liberation of HF during the reaction is unequivocally proved by the addition of one more equivalent of SIPr, which leads to the imidazolium salt with the HF2− anion. To functionalize 2, the latter reacted with B(C6F5)3 to give an unusual donor–acceptor compound, where the fluoride atom from the C6F5 moiety coordinates to B(C6F5)3 and the carbanion moiety remains unaffected. Such coordination susceptibility of the fluoride atom of a nonmetallic system to a main‐group Lewis acid (Fnon‐metal→BR3) is quite unprecedented.
Keywords: C-F activation; carbanions; N-heterocyclic carbenes; structure elucidation; Ylides

Saturated N-heterocyclic carbene based thiele's hydrocarbon with a tetrafluorophenylene linker - Kundu, Gargi; De, Sriman; Tothadi, Srinu; Das, Abhishek; Koley, Debasis; Sen, Sakya S. (Chemistry-A European Journal, 2019)
The synthesis of a SIPr [1,3-bis(2,6-diisopropylphenyl)-imidazolin-2-ylidene] derived Kekule diradicaloid with a tetrafluorophenylene spacer (3) has been described. Two synthetic routes have been reported to access 3. The cleavage of C-F bond of C6F6 by SIPr in the presence of BF3 led to double C-F activated compound with two tetrafluoro borate counter anions (2), which upon reduction by lithium metal afforded 3. Alternatively, 3 can be directly accessed in one step by reacting SIPr with C6F6 in presence of Mg metal. Compounds 2 and 3 were well characterized spectroscopically and by single-crystal X-ray diffraction studies. Experimental and computational studies support the cumulenic closed-shell singlet state of 3 with a singlet-triplet energy gap (Delta ES-T) of 23.7 kcal mol(-1).
Keywords: C-F activation; Density functional calculations; fluorine; Kekule diradicaloids; saturated NHC